Role of Smart Grid Connection in Renewable Energy Sources (International Journal of Food and Nutritional Sciences, 2022)
One of the many advantages of smart grid technology is a more cost-effective and effectively run electrical system. The main advantage of smart grid technologies, which is the subject of this paper, is that they make it possible to integrate significant amounts of renewable energy into an electricity system. By expanding the capacity of grid-connected sources of clean energy like solar energy, wind energy, as well as photovoltaic systems, modern grid approaches increase the quantity of fluctuating electricity production in the power grid. Secondly, smart grid encourages power distribution energy efficiency. The primary innovations for applications in smart grids are renewable energy sources (RESs) as well as energy storage systems (ESSs), which offer excellent prospects to reduce carbon emissions in metropolitan areas, control frequency and voltage aberrations, and respond to emergency situations whenever the liabilities exceed the production. However, the erratic nature of renewable energy sources and their inherent intermittency place enormous strain on power networks are disused. This study focuses on the role and importance of smart grid in renewable energy. The results conclude that smart grids plays a crucial role in smart grid connection by improving the efficiency and the performance of distribution system which will helps to improve electric supply in future.